2012
DOI: 10.1093/ntr/nts234
|View full text |Cite
|
Sign up to set email alerts
|

Urban Chinese Smokers From Lower Socioeconomic Backgrounds Face More Barriers to Quitting: Results From the International Tobacco Control-China Survey

Abstract: Research findings on social disparities in barriers to quitting faced by smokers from mainly Western Englishlanguage countries may or may not generalize to smokers in China. This paper sought to determine whether nicotine dependence, quitting self-efficacy, quitting interest differ by socio-economic status (SES), and whether they mediate the relationship between SES and quitting behavior of urban Chinese smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Our analyses were adjusted for such potential individual-level demographic confounders as age, gender, ethnicity, educational level, and occupation, all of which have been shown to be related to smoking and smoking cessation in China (e.g., Gruder et al, 2013;Li et al, 2011;Yang et al, 2014;Yong et al, 2013).…”
Section: Individual-level Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses were adjusted for such potential individual-level demographic confounders as age, gender, ethnicity, educational level, and occupation, all of which have been shown to be related to smoking and smoking cessation in China (e.g., Gruder et al, 2013;Li et al, 2011;Yang et al, 2014;Yong et al, 2013).…”
Section: Individual-level Independent Variablesmentioning
confidence: 99%
“…Two variables relating to level of urban economic development were also included; Gross Domestic Product (GDP) per capita (o 40,000, 40,000-49,999, 50,000 þ yuan) and disposable income per household (o 20,000, 20,000-29,999, 30,000 þ yuan). Living in a high income community has been found to be protective of smoking in China (Cai et al, 2013), independent of individual income characteristics, which have also been shown to be important (Yong et al, 2013). The city-level and provincial data were obtained from the National Bureau of Statistics (2013).…”
Section: Provincial and City-level Independent Variablesmentioning
confidence: 99%
“…These findings support other studies that show higher quit intention and successful cessation prevalence rates among groups of higher social status. 12,13 This phenomenon will complicate tobacco control in China further where health resources and social benefits are unequally allocated among the subpopulations. 36,37 The disadvantaged social groups that are marginalized already by a lack of health resources, will be burdened additionally by smoking-attributed health problems.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on urban dwellers because more than half of China's population resides in cities. We hypothesized that a range of personal and environmental determinants, such as social and economic status, 12,13 smoking patterns and nicotine dependence, 7,14,15 and smoke-free rules in public venues, 2 would affect smokers' intention to quit and their chances to be successful at quitting. Given the fact that cigarette gifting is an important social custom in China, [16][17][18] we also hypothesized that gifted cigarette users may have a lower rate of smoking cessation than those who primarily rely on purchasing their own cigarettes.…”
mentioning
confidence: 99%
“…Research finds that lower compared to higher socioeconomic status (SES) is related to greater TC obstacles including psychological and behavioral (Yong et al, 2013), less intent to quit tobacco use, and less abstinence from tobacco at both one and six months follow-up (Reid et al, 2010). Concurrently, low-income individuals have less access to health care in general, and TCS in particular (American Legacy, 2010).…”
Section: Demand For Tobacco Cessation Services Among Low-income Sud Pmentioning
confidence: 99%